Understanding and Implementation of Corporate Social Responsibility in the Context of Nigerian SMEs - Anakwue, Obianuju (2012)
ABSTRACT This research primarily focuses on small and medium scale enterprises (SMEs) in Nigeria and how they fit into the CSR space. The attention on the CSR discourse which has been mainly focused on large corporations and multinational companies cannot be overemphasised, but the increasing relevance of SMEs as potential contributors to economic growth and development has begun to attract attention for SMEs in the CSR literature and research. This study begins with an overview of the CSR literature, while highlighting a brief profile of Nigeria in order to shed light on the business environment, and while also pointing out the characteristics that are peculiar to SMEs. The study is qualitative in nature, using semi-structured interviews/focus group discussions; the study tries to investigate how SMEs in Nigeria understand CSR, how they implement it and what the motivation factors are. The findings are presented and thus reveal that CSR is dominantly viewed as philanthropy by SMEs and this is influenced by their religious beliefs and practices. It is anticipated that this study would serve as a baseline for future research on SMEs and CSR in Nigeria.